World Heritage: Where Are We? An Empirical Analysis - Bruno S. Frey; Paolo Pamini (Center for Research in Economics, Management and the Arts (CREMA), 2009)
An empirical overview of the UNESCO World Heritage List according to various characteristics is presented. The officially stated intention of the World Heritage List is to protect global heritage. Our focus is on the imbalance of the existing List according to countries and continents. The existing distribution is compared to hypothetical distributions considered ?balanced? from different points of view. It turns out that the World Heritage List is unbalanced with respect to a distribution of Sites according to population, area or per capita income. This paper wants to reveal facts about the existing distribution, and is designed to help a reasoned discussion to emerge.
Keywords: Z11; D6; F5; H87; 330; Global public good; World Heritage; Cultural Certificates; Monuments; UNESCO